Gephyrin, the enigmatic organizer at GABAergic synapses - Tretter, Verena E.; Mukherjee, Jayanta; Maric, Hans M.; Schindelin, Hermann; Sieghart, Werner; Moss, Stephen J. (Frontiers in Cellular Neuroscience, 2012)
GABAA receptors are clustered at synaptic sites to achieve a high density of postsynaptic receptors opposite the input axonal terminals. This allows an efficient propagation of GABA mediated signals, which mostly result in neuronal inhibition. A key organizer for inhibitory synaptic receptors is the 93 kDa protein gephyrin that forms oligomeric superstructures beneath the synaptic area. Gephyrin has long been known to be directly associated with glycine receptor β subunits that mediate synaptic inhibition in the spinal cord. Recently, synaptic GABAA receptors have also been shown to directly interact with gephyrin. Gephyrin-interacting domains have been identified and mapped within the intracellular loops of the GABAA receptor α1, α2, and α3 subunits. Gephyrin-binding to GABAA receptors seems to be at least one order of magnitude weaker than to glycine receptors and most probably is regulated by phosphorylation. Gephyrin not only has a structural function at synaptic sites, but is also a platform for multiple protein-protein interactions, bringing receptors, cytoskeletal proteins and downstream signalling proteins into close spatial proximity.